Investigating the trend of changes in the eastern county\'s of Lake Urmia and identification of areas capable of cultivating saline plants using remote sensing and GIS - Rahimeh Rostami; Ali Mohammad Khorshiddust; Mohammadreza Nikjoo; Hassan Mahmudzadeh (تحقیقات کاربردی علوم جغرافیایی)
The drying of Lake Urmia has had many environmental impacts on the surrounding areas of the lake. In this research, efforts have been made to identify vegetation coverings that are compatible with the study area and then it use of multiplicative decision-making models for identify areas susceptible to cultivation of these products. In the present study, following the study of species in the region of rapeseed, was selected as a suitable halophytes plant. Initially, using Landsat 5 and 8 images, the changes in the land use type and vegetation cover type of the region were investigated from 2000 to 2016, and after calculating the changes, the potential planting of the halophytes plant was sought. The ANP Fuzzy method was used to estimate the ability to cultivate rapeseed. Main criteria used in this research are topography, soil and meteorology. The topographic sub criteria are included: height, slope and tilt direction, soil criteria including soil texture, soil salinity, and soil pH and soil organic matter. Finally, the criteria for meteorological data are total annual precipitation, Relative humidity, average annual temperature, maximum annual temperature and annual minimum temperature. These layers first be changed to fuzzy and then, applying the weight of each of the following criteria, a map of the main criteria of soil, topography and meteorology was prepared and finally, by combining these three main parameters, the potential mapping was obtained. The results indicate a 25.43 percent reduction in water content and an increase of 21.03 percent in saline areas between 2000 and 2016, and the results of identifying areas susceptible to cultivation of halophytes plants have identified 14.28 percent of the study area suitable for rapeseed cultivation.